Peran Proses dalam Bauran Pemasaran Jasa Pendidikan terhadap Keputusan Mahasiswa Memilih Program Studi PGSD - Najib, Khotim Hanifudin; Nofrida, Eka Ridha; Budiarto, Sulistyo (UMSU, 2024)
In the era of increasingly fierce global competition, higher education institutions are required to enhance their marketing strategies to attract prospective students. The Primary School Teacher Education (PGSD) program is one of the popular programs, but students' decisions to choose this program are influenced by various factors in the education service marketing mix. This study aims to analyze the influence of the education service marketing mix on students' decisions to choose the PGSD program. This research uses a quantitative approach with a sample of 186 students from the 2022 and 2023 cohorts. Data were collected through a survey using Google Forms and analyzed using multiple regression analysis techniques. The education service marketing mix examined consists of seven elements: Process, Price, Promotion, Place, People, Product, and Physical Evidence. The results show that partially, only the process element significantly influences students' decisions to choose the PGSD program. Other elements such as price, promotion, place, people, product, and physical evidence do not show significant individual influence. However, simultaneously, the entire education service marketing mix significantly influences students' decisions to choose the PGSD program, with a contribution of 68%. This indicates that while some elements are not significant individually, the overall combination of the marketing mix elements still has a meaningful impact. These findings suggest that improving the quality of processes in delivering educational services, can increase students' interest in choosing the PGSD program. Therefore, educational institutions are expected to focus on enhancing process aspects to attract more prospective students. Additionally, even though other elements do not show significant partial effects, it is still important to consider the entire marketing mix in educational marketing strategies.